Determination of multi-criterion optimization features in creating systems for recomplexing anhydrous cosmetics - Ivanishena, Tetiana; Chereshnia, Zoriana; Mahdiichuk, Anna (Eastern-European Journal of Enterprise Technologies, 2026)
This study explores formulation systems for anhydrous cosmetics, specifically, solid shampoos. They have predicted quality indicators and a high level of resource efficiency. The main issue in designing such systems is the high complexity of optimization, due to technological contradictions between the product’s functional effect, physicochemical stability, environmental safety indicators, and composition. This work identifies features of the multi-criteria optimization method based on the Harrington desirability function for such systems. It involves normalizing experimental indicators and aggregating them into an integrated quality indicator D. Based on this indicator, the formulation composition of sample S2 is the most balanced across all criteria. The results are attributed to synergistic interactions among composition components and the establishment of a nonlinear dependence between the composition and properties. It has been shown that the desirability function successfully describes such interactions. It is shown that the deviation of at least one criterion beyond the limits of acceptability leads to a sharp decrease in the integrated assessment. The use of multi-criteria optimization based on the Harrington desirability function minimizes subjectivity and enables the comparison of alternative compositions of formulation technological systems. Multi-criteria optimization using the Harrington desirability function could be applied at the stage of laboratory design of environmentally friendly formulation systems, provided that technological regimes are adhered to and an identical raw material base is used